Integration and differentiation in science and their practical significance - Siusiuka E.N.; Ivanov D.L. (SHS Web of Conferences, 2023)
The article deals with the laws of dialectics, methods of cognition in science, integration and differentiation as two components of science advancement. The factors causing uneven development of these components are presented. General laws specific for various dynamic systems and forms of movement, general principles of understanding the surrounding world, which enable to combine knowledge of various subjects into a single, integral, harmonious system are presented. The authors of the article emphasise the need to integrate science, education and production, and identify the main problems that arise when implementing integrative programs. The competence-based approach in education, the need to focus on professional qualities, the socio-cultural orientation of the individual, intellectual maturity, and making non-standard decisions are emphasized. Systematization and interdisciplinary differentiation of the components of professional skills, which indicates the development of modern science, the engine of which is differentiation and integration are important for the integration of science and education.